A novel strategy combining electrospraying and one-step carbonization for the preparation of ultralight honeycomb-like multilayered carbon from biomass-derived lignin. (July 2021) - Cao, Meilian; Wang, Qingxiang; Cheng, Wanli; Huan, Siqi; Hu, Yi; Niu, Zhaoxuan; Han, Guangping; Cheng, Haitao; Wang, Ge
Abstract: Despite the great advantages of interconnected porous architectures of three-dimensional carbon as functional materials, apparent common drawbacks restricting their widespread applications are high cost and non-renewable of the carbon precursors and complicated activation procedures. In this study, biomass-derived honeycomb-like multilayered carbon (HMC) is synthesized by electrospraying and direct carbonization for the first time. Poly (methyl methacrylate) (PMMA) is mixed with biomass-derived lignin, the only carbon source, to form lignin/PMMA microspheres and microbowls by electrospraying. One-step carbonization of prepared micromaterials to obtain ultralight HMC, and the microstructures and pore size of carbon materials are controllable by adjusting the applied voltage of electrospraying. The obtained HMC-13 by carbonization of lignin/PMMA microspheres possesses interconnected carbon skeleton, partially graphitized structure and hierarchical pore system composed of macropores, mesopores and micropores. Benefiting from the structural advantages, HMC-13 as electrode of supercapacitor delivers a high specific capacitance of 348 F g −1 at 0.5 A g −1 in aqueous electrolytes. Additionally, the supercapacitor exhibits excellent cycling stability with only 4% capacitance loss after 10 000 cycles. Based on these encouraging results, environmental friendliness and facile synthesis strategy, the biomass-derived ultralight porous carbon material holds great promise for facilitating wasted biomass utilization and developing sustainable energy products. Graphical abstract: Image 1 Highlights: A strategy combining electrospraying and carbonization to get carbon was developed. The synthesized ultralight carbon possessed honeycomb-like multilayered structure. The obtained carbon had partially graphitized structure and hierarchical pore system. The prepared carbon as electrode exhibited excellent electrochemical performance.